2020
DOI: 10.47197/retos.v0i39.81060
|View full text |Cite
|
Sign up to set email alerts
|

Ejercicio físico aeróbico y atención selectiva en escolares de educación primaria (Aerobic physical exercise and selective attention in primary school children)

Abstract: El ejercicio físico puede tener efectos beneficiosos sobre las funciones cognitivas y el rendimiento académico. Entre las funciones cognitivas, el estudio de la atención en escolares ha adquirido un especial interés por su posible influencia en aspectos concretos tales como el rendimiento académico o la integración social. El objetivo fue analizar el efecto agudo de una sesión de ejercicio físico aeróbico sobre la atención selectiva en una muestra de 48 niños y 40 niñas (Edad, M ± DT = 9.48 ± .505 años). Se em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 41 publications
0
6
0
1
Order By: Relevance
“…76 %). In relation to articles that evaluated physical fitness, the studies by Rosa et al (2021) and Pérez-Lobato et al (2016) argue that adolescents who had better aerobic fitness and physical fitness respectively presented better selective attention. No study reported a decrease in attention after PA implementation.…”
Section: Main Characteristics Of the Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…76 %). In relation to articles that evaluated physical fitness, the studies by Rosa et al (2021) and Pérez-Lobato et al (2016) argue that adolescents who had better aerobic fitness and physical fitness respectively presented better selective attention. No study reported a decrease in attention after PA implementation.…”
Section: Main Characteristics Of the Studiesmentioning
confidence: 99%
“…Regarding the types of attention, selective attention was the dimension that was most evaluated in the studies with 19 of the 33 articles (57%). Of the 19 articles that evaluated selective attention, 12 (63%) claimed an improvement in its levels in relation to the initial parameters, these interventions varied in number of sessions between one single session (Rosa et al, 2021) up to 12 weeks (about three months) with two weekly sessions (Martínez-López et al, 2018). Similarly, the intensities and timing of the applications varied, ranging from four minutes of high-intensity activities (Ma.…”
Section: Main Characteristics Of the Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, several studies show how through Physical Education and movement there are improvements in different areas such as: selective attention and inhibitory control in Primary Education (Rosa et al, 2020;Rosa et al, 2021); the motivation of young children to learn English vocabulary through singing, dancing and physical movement (Pacheco et al, 2022); vocabulary acquisition and in the retrieval of long-term memory in second languages (Padial et al, 2022); socio-affective skills and violence prevention in Primary Education (Aguilar et al, 2021); cognitive functions of the elderly (Romero et al, 2021), as well as in their quality of life through active aging (Martínez et al, 2021); Attention deficit hyperactivity disorder (ADHD) symptoms, and more significantly inattention (Palma et al, 2021); psychomotor and linguistic development in early care (Zambrano et al, 2022); or basic locomotor motor skills (Pérez et al, 2022).…”
Section: Introductionmentioning
confidence: 99%